Improving Students’ Vocabulary Mastery Through Folktale Storises at SMP Al-Azhar Mandiri Palu - Mardianto Bidolong; Saripah Fadilah; Ani Rahmayani A. Nape (EDUKASI, 2023)
The development of vocabulary mastery is an important goal of teaching English. One of the approaches that are effective in fostering the vocabulary mastery is using folktale stories. The objective of this research is to prove that the use of folktale stories can improve the vocabulary mastery of the first year students of SMP Al-Azhar Mandiri Palu. The sample was taken through random sampling technique. The data were collected by using two kinds of instrument: observation and test. The data observation was analyzed descriptively, whereas the data of the test was analyzed by using statically analysis. After conducting the observation and test, the writers found that the students have good motivation in learning and the result of the data analysis showed that there was significance difference between pre-test and post-test. It is revealed by the hypothesis of the research stated that the vocabulary mastery of the first year student of SMP Al-Azhar Mandiri Palu can be improved by applying folktale stories. This hypothesis was accepted after testing it, in which t-counted value 4.18. By applying the 0, 05 level of significance and 72 degree of freedom with the critical value of the t-table through interpolation computation is 1.996. The result of t-counted value is greater than t-table values. It means that the alternative hypothesis (Ha) is accepted and the Null hypothesis (Ho) is rejected. The writers concludes that the use of folktale stories can improve the vocabulary mastery of the first year student of SMP Al-Azhar Mandiri Palu.